A Literature Informal Learning Review: Social Media Platform to Improve Corporate Citizen Knowledge - Fredson Kotamena; Martinus Tukiran (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
In this research we aim to examine the social media’ platforms, companies use for informal learning, and the differences between generations in companies, on the usage of social media platforms. Before we started the review, we identified the main topics in informal learning. Then, we continued to conduct literature reviews to identify relevant literature and extract information on the practice of social media as an informal learning tool to gain knowledge. The value of social media as a medium of learning is also open freely to every element in the organization. Companies also build their intranet networks (Enterprise Social Media) to share projects that are more confidential. While intergenerational differences in behavior towards the practice of social media as a means of informal learning are not empirical available, and we would need further research. The different generation had a different approach in life, and it practically would be impacted to how they use their social media in daily activity; including as a learning tool.